Cementless Implantation of Zweymueller-Endler Total Endoprostheses of the Hip - Clinical, Radiological and Scintigraphic Follow-Up for 2 Years - Schicha, H.; Perner, K.; Voth, E.; Reith, H. G.; Willert, H. G.; Emrich, D. (Nuklearmedizin - NuclearMedicine, 1986)
Sixty-four patients with cementless Zweymueller-Endler total endoprostheses of the hip underwent follow-up postoperatively for 2 years. In 3 patients loosening or infection occurred. In 61 patients no complications were observed. However, in 74% of these patients increasing activity uptake at the tip of the shaft was found by scintigraphy. This was associated with hypertrophy of the corticalis and/or with a marrow cavity reaction, observed radiologically. The results show that scintigraphic evaluation of cementlessly implanted Zweymueller-Endler endoprostheses of the hip must be interpreted differently compared to isoelastic or to cemented prostheses.